Easy performance of 6-color confocal immunofluorescence with 4-laser line microscopes - Eissing, Nathalie; Heger, Lukas; Baranska, Anna; Cesnjevar, Robert; Büttner, Maike; Söder, Stephan; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana (Immunology Letters, 2014)
Confocal laser scanning microscopy is an advanced technique for imaging tissue samples in vitro and in vivo at high optical resolution. The development of new fluorochrome variants do not only make it possible to perform multicolor flow cytometry of single cells, but in combination with high resolution laser scanning systems also to investigate the distribution of cells in lymphoid tissues by confocal immunofluorescence analyses, thus allowing the distinction of various cell populations directly in the tissue. Here, we provide a protocol for the visualization of at least six differently fluorochrome-labeled antibodies at the same time using a conventional confocal laser scanning microscope with four laser lines (405 nm, 488 nm, 555 nm, and 639 nm laser wavelength) in both murine and human tissue samples. We further demonstrate that compensation correction algorithms are not necessary to reduce spillover of fluorochromes into other channels when the used fluorochromes are combined according to their specific emission bands and the varying Stokes shift for co-excited fluorochromes with the same laser line.
EVALuna2:6626